Предмет: Математика,
автор: karinaasanova769
4) 3(2x - 1) + 6x = 10x - 7;
5) 0,3(x - 4) - 0,7x = -2;
6) 0,6(5 + 2x) - 2 = 0,2x;
Ответы
Автор ответа:
8
Пошаговое объяснение:
4)3(2х-1)+6х=10х-7 6х-3+6х=10х-7
6х+6х-10х=(-7)+3 2х=(-4) х=(-4)÷2 х=(-2)
5)0,3(х-4)-0,7х=-2 0,3х-1,2-0,7х=-2
-0,4х=-2+1,2 -0,4х=-0,8 х=-0,8÷-0,4 х=2
6)0,6(5+2х)-2=0,2х 3+1,2х-2=0,2х
1,2х-0,2х=-3+2 х=-1
Похожие вопросы
Предмет: Алгебра,
автор: hortanastasia763
Предмет: Английский язык,
автор: n41287322
Предмет: Геометрия,
автор: ajsuluabutalipova153
Предмет: Алгебра,
автор: alyaalinaagaf1
Предмет: Биология,
автор: tima0221